The depression and anxiety levels and temperament characteristics of the mothers of children with asthma - Kiliç, Nülüfer; Kiliç, Mehmet (Ondokuz Mayis Universitesi, 2023)
In our study, we planned to compare the depression, anxiety levels, and dominant temperament characteristics of mothers of children with asthma with mothers of healthy children. The mothers of a total of 114 children who had asthma and mothers of 100 healthy children were included in the present study. The Sociodemographic Data Form, Beck Depression Inventory (BDI), Beck Anxiety Inventory (BAI), and TEMPS-A (Temperament Evaluation of Memphis, Pisa, Paris, San Diego Auto Questionnaire) were applied to the participants. The Asthma Quality of Life Questionnaire (PAQLQ) and Asthma Control Test (AKT) were also performed to have information on the disease for children with asthma. No significant differences were detected between the mean age of the children included in the study and their mothers (p>0.05). The participants’ marital status, education status, income status, employment status, number of children, and the number of people living at home were similar (p>0.05). Although the smoking rate of the mothers of children who had asthma was 28.1%, the rate of smoking of the mothers in the control group was 12% (p<0.05). Irritable temperament, anxious temperament traits, and BAI scores were significantly higher in mothers of children with asthma (p<0.05). BAI scores were higher in mothers of children with multiple inhalant allergies and using high-level drugs according to the GINA (Global Initiative for Asthma) guideline (p<0.05). In our study, we found that irritable temperament, anxious temperament characteristics, and anxiety scores increased in mothers of children with asthma. Therefore, in addition to the asthma treatment of children, the application of psychological support programs to mothers should be considered. © 2023 Ondokuz Mayis Universitesi. All rights reserved.
Keywords: anxiety; asthma; depression; mother; temperament